Metabolites Role in Detecting Brain Tumors Using Nuclear Magnetic Resonance Spectroscopy and Comparing Their Densities in Tumoral Patients with Those in Healthy Individuals - Farahnaz Azarakhsh; Vahid Changizi (Tehran University of Medical Sciences, 2016)
Background and Aim: Brain tumors have remained as a significant cause of morbidity and mortality and are often refractory to treatment. The grading of brain tumor has an important implication in clinical management. Currently, magnetic resonance spectroscopy (MRS) is an important dimension in evaluating metabolites and grading brain tumors. The aim of this study is to evaluate metabolites in brain tumors and grading brain gliomas using HMRS (proton magnetic resonance spectroscopy). Materials and Methods: Studies were performed using single voxel MRS, at a field strength of 3Tesla and pulse sequence using point resolved single volume spectroscopy (PRESS) with repetition time (TR) 1000-6000ms and echo time (TE) 36-136ms, and distinguished metabolites including Choline (Cho), Creatin (Cr), and N-acetyl aspartate (NAA) were detected. Results: Thirty-seven cases (17 males and 20 females) had data which passed quality control. The patients' age ranged from 7 to 81 years with a mean of 41.46±2.78. MRS data were processed using SYNGO software in terms of mean spectra and metabolite concentrations which were compared using minitab and SPSS. Signiﬁcant differences were found in concentrations of key metabolites, and Cho/NAA and Cho/Cr ratios using t-test with a significance level (α≤0.05). In the assessment of age rate and tumor grading, the malignancies of brain tumors did not correlate with patients' age and sex. Conclusion: MRS can detect subtle differences between low-grade brain tumors in children and should form part of the clinical assessment of these tumors.